2020
DOI: 10.15829/1560-4071-2020-3766
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various classes of glucose-lowering medications on the blood vessel elasticity in patients with type 2 diabetes

Abstract: Aim. To study the effect of various classes of glucose-lowering agents (dipeptidyl peptidase-4 (DPP-4) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors) on the vascular stiffness in patients with type 2 diabetes (T2D) and high cardiovascular risk.Material and methods. The open-label, prospective 24-week study included 120 patients with T2D and high cardiovascular risk. We evaluated the effect of modern glucose-lowering medications, empagliflozin at a dose of 25 mg/day (SGLT-2 inhibitor) and sitagliptin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Figure 1 outlines the search and selection process. Of the 13 included studies [8][9][10][11][12][13][14][15][16][17][18][19][20] (Table 1), 8 were case-control experimental studies and 5 were prospective experimental studies evaluating the changes in CRP before and after treatment with SGLT-2 inhibitors among patients with T2DM (Table 2); these studies were published from 2016 to 2021 and included data for a total of 927 patients. The quality of studies was evaluated with Newcastle-Ottawa Quality Assessment Scale, as shown in Table 3.…”
Section: Data Collectionmentioning
confidence: 99%
“…Figure 1 outlines the search and selection process. Of the 13 included studies [8][9][10][11][12][13][14][15][16][17][18][19][20] (Table 1), 8 were case-control experimental studies and 5 were prospective experimental studies evaluating the changes in CRP before and after treatment with SGLT-2 inhibitors among patients with T2DM (Table 2); these studies were published from 2016 to 2021 and included data for a total of 927 patients. The quality of studies was evaluated with Newcastle-Ottawa Quality Assessment Scale, as shown in Table 3.…”
Section: Data Collectionmentioning
confidence: 99%